EVALUATION OF Salmonella pullorum SHEDDING IN JAPANESE QUAILS (Coturnix coturnix) - Roberta Cristina Rocha-e-Silva; William Maciel Cardoso; Adonai Aragão Siqueira; Régis Siqueira de Castro Teixeira; Átilla Holanda Albuquerque; Ruben Vasconcelos Horn (Ciência Animal Brasileira, 2016)
Salmonella Pullorum is a pathogen that infects several species of birds, mainly offspring, and among them, quails. Therefore, this study was performed in order to evaluate the S. Pullorum shedding in experimentally infected Japanese quails (Coturnix coturnix) and egg contamination ability. S. Pullorum ATCC lyophilized was inoculated in all birds (60 quails at 160 days). Before  the inoculation, rapid slide agglutination test was performed in all birds and individual cloacal  swabs were collected randomly. Birds from group A and group B received 0.5mL of inoculum containing 1.5x102 CFU and 7.5 x 108 CFU of S. Pullorum, respectively, directly in the crop. The cloacal swab samples were collected on 3, 6, 9, 16 and 23 days post-inoculation (dpi) and all eggs were collected. Positive cloacal swab samples were initiated at the 3rd dpi. A total of 30 pool of   eggs was analyzed, of which 73% positive for S. Pullorum until the 16th dpi. In conclusion, adult Japanese quails are possibly more resistant to the infection by S. Pullorum, but they can shed this pathogen in the environment as  well.